Ulcerative colitis and HLA phenotype. Issue 9 (September 1985) - Cottone, M; Bunce, M; Taylor, C J; Ting, A; Jewell, D P
Abstract : The distribution of HLA A, B, C, DR antigens was investigated in a British population with ulcerative colitis. Fifty six patients were typed for HLA, A, B, C and 46 additionally for DR. No association was found between the HLA phenotype and the presence or absence of ulcerative colitis. Serum from 52 patients was tested for the presence of the anticolon antibody. There was no relation between the presence of the antibody and the HLA phenotype. Finally, no correlation was found between the HLA phenotypes, the age of onset of the disease, the extent and the clinical course.